2016
DOI: 10.1007/s10753-016-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3, Regulatory T Cell, and Autoimmune Diseases

Abstract: Regulatory T cells (Tregs) represent a cell type that promotes immune tolerance to autologous components and maintains immune system homeostasis. The abnormal function of Tregs is relevant to the pathogenesis of systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and other autoimmune diseases. Therefore, therapeutic modulation of Tregs could be a potent means of treating autoimmune diseases. Human Tregs are diverse, however, and not all of them have immunosuppressive effects. Forkhead box P3 (Foxp3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 140 publications
1
66
0
5
Order By: Relevance
“…Defects in the number or function of Tregs led to various autoimmune diseases and graft rejection, including SLE, rheumatoid Arthritis (RA) and graft-versus-host disease (GVHD) [4,6,27,28]. It was reported that patients with a defect in CD4+FoxP3+ Tregs developed lupus nephritis [29] and that the ratio of FoxP3 + / CD3 + cells was significantly reduced in kidney biopsies of patients with lupus nephritis [30].…”
Section: Foxp3mentioning
confidence: 99%
“…Defects in the number or function of Tregs led to various autoimmune diseases and graft rejection, including SLE, rheumatoid Arthritis (RA) and graft-versus-host disease (GVHD) [4,6,27,28]. It was reported that patients with a defect in CD4+FoxP3+ Tregs developed lupus nephritis [29] and that the ratio of FoxP3 + / CD3 + cells was significantly reduced in kidney biopsies of patients with lupus nephritis [30].…”
Section: Foxp3mentioning
confidence: 99%
“…Our result for FOXP3 rs3761548 polymorphism in grade 4 knee OA patients showed that subjects carrying the C variant allele were at higher risk for knee OA in codominant, dominant and overdominant genetic models. Previous studies have shown that functional FOXP3 variants cause several immune‐related disorders, including RA, systemic lupus erythematosus, autism, multiple sclerosis and preeclampsia, probably by changing FOXP3 expression and/or function . Moreover, FOXP3 rs3761548 AA genotype has been found to be associated with Behcet's disease, RA and spontaneous abortion in a Chinese Han population .…”
Section: Discussionmentioning
confidence: 98%
“…The main function of Treg is to inhibit the excessive activation of effector T cells and prevent immune damage to the body (Wahren‐Herlenius & Dorner, ). Decreased number and dysfunction of Treg cells are often found in AIDs (Tao et al, ). Among cell surface molecular markers, Treg cell is often defined as CD4 + CD25 + FOXP3 + CD127 low T‐cell subgroup (Dominguez‐Villar & Hafler, ).…”
Section: Introductionmentioning
confidence: 99%